SYMPATHY ACTION SAFETY DRIVING CAMPAIGN IN PREVENTING TRAFFIC ACCIDENTS ON GO-JEK COMMUNITY RIDERS IN MEDAN CITY: AKSI SIMPATI KAMPANYE SAFETY DRIVING DALAM MENCEGAH KECELAKAAN LALU LINTAS PADA PENGENDARA GO-JEK COMMUNITY DI KOTA MEDAN - Umi Salmah; Arfah Mardiana Lubis; Isyatun Mardhiyah Syahri; Yenny Obsi Satra (Yayasan Education and Social Center, 2022)
A social service was held on Go-Jek Community Medan and Go-Jek Brother Community Medan Basis Sekata. Based on the initial survey, the partner's problem is lack of knowledge so partners need knowledge through assertive communication by looking for agents. The agents were responsible in doing a safety driving campaign act which they had fulfilled the integrity facts previously. For the problem experienced by the partners, the early phase was held through the socialization of safety driving signpost framing in two partners, continued by choosing the agent who would campaign safety driving. The chosen agent would share the stickers and safety driving modules to Go-Jek Community. The agent was expected to do the socialization by spreading the stickers and modules to Go-Jek Community. This activity would be evaluated by the agent and the report was taken after 3 months of the social service of USU. The result of this social service described the concern to Go-Jek drivers’ safety, and it got the positive respond from each Go-Jek Community. On the evaluation phase, this social service was successfully done and it successfully increased the knowledge, as well as changed the behavior of Go-Jek driver’s safety in riding their bikes